Agrotech / Mario Helmie Joeharee... [et al.] - Abdul Rajak, Mohammad Azri; Monnie, Rye Poloniuss; Marasantu, Mohd Azim; Mandu, Sitti Nurhaya; Joeharee, Mario Helmie (2016)
Agrotech, is a re-seller company that focus more onto sell an organic fertilizer. This a new company that created base on partnership agreement that consist of 5 member where all of them work for the company as the top manager, Where one of them work as the general manager since he had contribute more than the other as what had been agree by all the partnership member. Our company would focus more onto Ranau district since the people at that are more onto plant a vegetable corps where this is a perfect opportunity for our vegetable fertilizer to be buy and use. Our company also is are seller company, where we buy the product from supplier then re-sell it back to the local people such as Ranau and other plantation area that want to use our fertilizer. Other than the 5 partnership member. Agrotech also employ 5 workers that would be under the responsibility of the operational manager to run the daily business other than the upper management responsibility. Lastly, The company also would directly entertain every customer that come to the business primes with a proper guide on how to take or give the customer brief discussion on how we run our business and the flow on how we conduct our sell to the customer. Based on what had been provided by the company it-self.